Protection of Passeriformes Birds in Wetland Ecological Restoration: A Case Study of the Reed Parrotbill (Paradoxornis heudei) in Baiyangdian - Qi Sun; Heng Wu; Taijun Zuo; Zengrui Tian; Jiaojiao Wang; Jianhua Hou (Diversity)
Due to the increasing impact of human activities on the environment, habitat loss, fragmentation, and degradation pose significant threats to bird diversity worldwide. Baiyangdian, the largest freshwater lake wetland in North China, is an important habitat for birds. The degradation of water quality caused by decaying reed rhizomes has prompted governmental initiatives for ecological restoration in Baiyangdian. However, it has also led to the significant destruction of reed habitats within the wetlands consequently. Bird species that rely on these reed habitats, especially the reed parrotbill, face a significant threat, necessitating the establishment of species reserves to mitigate the loss of bird diversity. Our research aims to identify the potential suitable habitats for the reed parrotbill in Baiyangdian and establish priority conservation areas. Using the environmental factors determined with Google Earth Engine (GEE), ultimately we designated the following areas as priority conservation zones: the Fuhe Wetland (FHW), the reed area south of Beihezhuang (BHV), both sides of the Baiyangdian Bridge (BYDB), the western shoreline of Shaochedian (SCD), Yannandi Park (YNDP), east of Guangdianzhangzhuang Village (GDZZV), east of Dongtianzhuang (DTV), north of Xilizhuang (XLV), south of Caiputai Village (CPTV), north of Gaolou Village (GLV), and the Xiaoyihe Wetland (XYW). Our findings provide a scientific reference for ecological restoration projects in the Baiyangdian region and offer supporting data for the conservation management of the reed parrotbill.